A Unique and Characteristic Cam FAI Morphology in Young Patients with Comorbid Inflammatory Conditions. (4th November 2020) - Seth, Akshay; Yen, Yi-Meng; Tourn, Diego; Smit, Kevin; Carsen, Sasha
Abstract : Background: The relationship between femoroacetabular impingement (FAI) and inflammatory medical comorbidities has not been established in the pediatric population. The purpose of this study was to investigate the prevalence of inflammatory conditions in pediatric patients with FAI and the morphology of the associated deformity. Methods: We performed a retrospective cohort study of 90 patients who were diagnosed with FAI in our institution's adolescent hip clinic from January 2016 to March 2018. Patients with an inflammatory comorbidity were identified. Standard quantitative radiographic FAI measurements as well as qualitative femoral head-neck junction morphology were analyzed. Results: Eight patients (8.9%) with 11 symptomatic hips were found to have an inflammatory condition. These 8 patients all had cam deformities. Nine of the symptomatic hips in this subset of patients had a negative femoral offset, where the cam deformity extended beyond the anterior margin of the femoral head. Qualitative assessment revealed a unique head-neck morphology with a prominent and "sharp-edged" bump at the head-neck junction, which resembled an inflammatory beak. In comparing patients with and without inflammatory comorbidities, a marked difference was found for alpha angles (difference, 26.6°; 95% confidence interval [CI], 18.2° to 35.0°) but not for age at diagnosis (difference, 0.5 years; 95% CI, −0.8 to 1.6 years) or the lateral center-edge angle (difference, 1.9°; 95% CI, −3.9° to 7.7°). Conclusions: At our institution, 8.9% of pediatric patients with FAI were found to have an inflammatory comorbidity. These patients presented with a characteristic prominent "sharp-edged" head-neck morphology that standard radiographic measurements captured as a negative femoral offset and a larger alpha angle than was seen in patients without systemic inflammatory disease. Awareness of the characteristic cam deformity that was found in these patients may help to identify patients with undiagnosed inflammatory conditions. This unique deformity also raises questions regarding the possible role of physeal inflammation in the development of cam deformities and indicates a need for additional studies to investigate the relationship between systemic inflammatory diseases and FAI. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.